2002
DOI: 10.1083/jcb.200206009
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes are predominantly located randomly with respect to each other in interphase human cells

Abstract: To test quantitatively whether there are systematic chromosome–chromosome associations within human interphase nuclei, interchanges between all possible heterologous pairs of chromosomes were measured with 24-color whole-chromosome painting (multiplex FISH), after damage to interphase lymphocytes by sparsely ionizing radiation in vitro. An excess of interchanges for a specific chromosome pair would indicate spatial proximity between the chromosomes comprising that pair. The experimental design was such that qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 33 publications
(56 reference statements)
9
60
2
Order By: Relevance
“…The major histocompatibility complex (MHC) class II locus protrudes from the HSA6 chromosome territory when actively transcribing [56,62] and preferentially extends into HSA1, 2 and 9 but not the HSA8 territory [62], indicating preferred neighbors of HSA6 in fibroblasts. The analysis of radiation-induced translocations in human lymphocytes further supports preferred relative positioning of chromosomes [87][88][89][90]. However, some of these studies find a randomness with respect to relative positioning overall, but find a cluster of gene rich chromosomes (HSA1, 16,17,19,22) in the nuclear interior [88,90].…”
Section: Relative Spatial Positioning Of the Genomementioning
confidence: 85%
See 2 more Smart Citations
“…The major histocompatibility complex (MHC) class II locus protrudes from the HSA6 chromosome territory when actively transcribing [56,62] and preferentially extends into HSA1, 2 and 9 but not the HSA8 territory [62], indicating preferred neighbors of HSA6 in fibroblasts. The analysis of radiation-induced translocations in human lymphocytes further supports preferred relative positioning of chromosomes [87][88][89][90]. However, some of these studies find a randomness with respect to relative positioning overall, but find a cluster of gene rich chromosomes (HSA1, 16,17,19,22) in the nuclear interior [88,90].…”
Section: Relative Spatial Positioning Of the Genomementioning
confidence: 85%
“…The analysis of radiation-induced translocations in human lymphocytes further supports preferred relative positioning of chromosomes [87][88][89][90]. However, some of these studies find a randomness with respect to relative positioning overall, but find a cluster of gene rich chromosomes (HSA1, 16,17,19,22) in the nuclear interior [88,90]. Arsuaga et al, [88] found evidence of a cluster of acrocentric, nucleolus-associated, chromosomes, whereas Cornforth et al, [90] did not find a significant level of clustering for these chromosomes.…”
Section: Relative Spatial Positioning Of the Genomementioning
confidence: 85%
See 1 more Smart Citation
“…It has been suggested that chromosomal loci prone to undergo interchromosomal exchanges may be positioned close to each other due to a nonrandom pairing of the respective chromosome territories (Cremer et al, 1996;Cornforth et al, 2002;Parada et al, 2002). When the genes involved in rearrangements are on the same chromosome, it is reasonable to postulate that structure of the chromatin within a territory determines the positioning of the genes with respect to each other.…”
Section: Discussionmentioning
confidence: 99%
“…A precise antiparallel positioning of chromosome sets was claimed for the mitotic rosette and interphase nuclei, thus advocating a separation of haploid genomes (Nagele et al 1995(Nagele et al , 1998(Nagele et al , 1999. While an antiparallel order could not be confirmed by other groups (Allison and Nestor 1999;Cornforth et al 2002;Bolzer et al 2005;Mayer et al 2005), whether or not parental genomes are separated in another pattern remained unclear.…”
Section: Introductionmentioning
confidence: 89%